2015
DOI: 10.1093/jxb/erv205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate flavonoid pathway genes using transcriptome correlation network analysis in ripe strawberry (Fragaria×ananassa) fruits

Abstract: HighlightThis work in strawberry fruit predicts new genes relevant to a key metabolic pathway using correlation analysis, and then demonstrates their function in a rapid and effective transient assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 30 publications
7
83
0
Order By: Relevance
“…The involvement of FaMADS9 in the regulatory system of flavonoid metabolism in the receptacles is supported by the number of TFs, previously reported to participate in the control of the pathway, the expression of which was altered in the FaMADS9 ‐silenced lines. These genes included MYB10 ( FvH4_1g22020 ), PCF1 ( FvH4_6g16170 ), DIV ( FvH4_6g11950 ), ZFN1 ( FvH4_6g00570 ) and ZFN2 ( FvH4_7g01060 ) (Pillet et al , ). The complex interaction among these regulatory genes in relation to flavonoid biosynthesis, as well as other developmental changes in ripening receptacles, requires the global analysis of available data sets associated with the process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The involvement of FaMADS9 in the regulatory system of flavonoid metabolism in the receptacles is supported by the number of TFs, previously reported to participate in the control of the pathway, the expression of which was altered in the FaMADS9 ‐silenced lines. These genes included MYB10 ( FvH4_1g22020 ), PCF1 ( FvH4_6g16170 ), DIV ( FvH4_6g11950 ), ZFN1 ( FvH4_6g00570 ) and ZFN2 ( FvH4_7g01060 ) (Pillet et al , ). The complex interaction among these regulatory genes in relation to flavonoid biosynthesis, as well as other developmental changes in ripening receptacles, requires the global analysis of available data sets associated with the process.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of MYB10 ( FvH4_1g22020 ), a gene involved in the regulation of the flavonoid pathway in strawberry fruits (Medina‐Puche et al , ), showed that the expression of this gene was significantly up‐regulated in the white receptacles (Table S2). Other TFs for which expression was correlated with flavonoid metabolism, such as TCP1 ( FvH4_6g16170 ), ZFN2 (FvH4_7g01060) and DIV (FvH4_6g11950) (Pillet et al , ), were down‐regulated in transgenic red receptacles (Table S2). In contrast, other genes associated with anthocyanin production in strawberry, such as the four members of the RAP family ( FvH4_1g27460 , FvH4_6g38760 , FvH4_2g25200 , FvH4_2g25210 ), encoding GST anthocyanin transporters (Luo et al , ), were up‐regulated in white receptacles of the silenced lines.…”
Section: Metabolic Changes In the Receptacles Of Famads9‐silenced Linmentioning
confidence: 99%
See 2 more Smart Citations
“…However, among the largest and most diverse gene families, the TCP gene family has not been systematically identified in the strawberry genome. To date, only the strawberry FaTCP11 gene has been shown to play a role in ripening and in the regulation of flavan-3-ols synthesis (Pillet et al, 2015). …”
Section: Introductionmentioning
confidence: 99%